1992
DOI: 10.1007/bf00130090
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield response of papaya to intercropping with vegetable crops in southwestern Nigeria

Abstract: At Ibadan, southwestern Nigeria, papaya trees were imercropped with okra, watermelon, sweet potato, bush greens, jews' mallow and Solanum gilo Raddi. The aim of the experiment was to select crops suitable for intercropping in the alleys of papaya plants in orchards. Sweet potato and Solanurn gilo Raddi caused marked reduction in the yield of papaya. Land Equivalent Ration (LER) for papaya intercopped with okra, water-melon, sweet potato, bush greens° jews' mallow and Solanum gilo Raddi were 3.86, 3.13, 2.06, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 3 publications
(2 reference statements)
1
7
0
1
Order By: Relevance
“…[61] had reported that intercrops are most productive when their component crops differ greatly in growth duration so that their maximum requirements for growth resources occur at different times. However, intercropping results generally in yield reduction of intercrops compared with the same crops grown sole [22] [62]. In this study, higher plant population in year II did not retard vine length increase but vine length decreased with increased plant population in year I.…”
mentioning
confidence: 50%
See 2 more Smart Citations
“…[61] had reported that intercrops are most productive when their component crops differ greatly in growth duration so that their maximum requirements for growth resources occur at different times. However, intercropping results generally in yield reduction of intercrops compared with the same crops grown sole [22] [62]. In this study, higher plant population in year II did not retard vine length increase but vine length decreased with increased plant population in year I.…”
mentioning
confidence: 50%
“…Moreover, intercropping offers the tropical farmers an early income from the annual vegetable intercrops before the main crop is harvested [22] [23]. [24] observed that annual vegetable crops such as celosia, okra and pepper occupy valuable ecological niche in tropical agriculture and play significant roles in the eco-physiology of mixed systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nedunchezhiyan et al 2012, Mangifera indica Mirjha et al (2016), Pyrus spp. Nerlich et al (2013) Morus alba Asati et al (2007) Zizyphus mauritiana Sereke et al (2014), Coffea arabica Iijima et al (2003) and Carica papaya Aiyelaagbe et al (1992) are mainly intercropped with Fabaceae, Solanaceae, Brassicaceae and Euphorbiaceae crops.…”
Section: Horti-olericulturementioning
confidence: 99%
“…A common intercropping combination in southwest Nigeria is maize/okra relay cropping followed by watermelon or bush greens and jute mallow or fodder crop of sweet potato. Okra is suitable for intercropping with papaya and it also now cultivated as an irrigated crop during the dry season, where it is often produced in mixed cropping with onion and other crops (Adelana, 1986;Aiyelaagbe & Jolaoso, 1992 Vol. 5, No.…”
Section: Literature Reviewmentioning
confidence: 99%